Heat absorber and secondary battery module equipped with said heat absorber
Patent Information
- Application Number
- JP2024571285
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-02-16
- Filing Date
- 2024-02-15
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2044-02-15
AI Technical Summary
【0007】 本開示の吸熱体によれば、吸熱開始温度が低く、吸熱量、難燃性及びクッション性に優れる。 本開示によれば、吸熱開始温度が低く、吸熱量、難燃性及びクッション性に優れる吸熱体を備えることにより、安全性の高い二次電池モジュールを提供できる。
Smart Images

Figure 0007640010000002 
Figure 0007640010000003 
Figure 0007640010000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat absorber and a secondary battery module including the heat absorber. [Background technology]
[0002] Secondary batteries, which can control the time difference between energy storage and demand, are used in a variety of applications including automobiles and mobile devices, and are becoming increasingly important as they are needed to expand the introduction of renewable energy from the perspective of building a low-carbon society and ensuring energy security. However, when the temperature of a secondary battery, such as a lithium-ion battery, rises due to heat generation during high-speed charging or high-output discharging, there is a risk of the battery being damaged by thermal runaway. Furthermore, as ultra-high-speed charging progresses in the future, it is predicted that the amount of heat generated will increase, and there is a demand for the development of a method for suppressing temperature rise in order to improve the safety of batteries. Secondary batteries can also go into thermal runaway due to internal short circuits, etc., which can cause problems such as fire or smoke. Therefore, in order to minimize damage caused by such defects, there is a demand for technology that can prevent or delay subsequent explosions in other battery cells by absorbing heat and extinguishing the fire from an abnormally hot battery.
[0003] For example, Patent Document 1 is an example of a technology that suppresses battery ignition and has excellent fire resistance. Patent Document 1 discloses a technology in which a battery exterior film having a fire-resistant resin layer containing a hydrated metal compound such as aluminum hydroxide or magnesium hydroxide as a heat-absorbing agent is used as an exterior material for a battery. Patent Document 2 is an example of a technology that can quickly extinguish a fire caused by a sudden temperature rise in a battery. Patent Document 2 discloses a technology related to a fire-resistant resin composition or a sheet thereof that contains a thermoplastic resin or an elastomer resin, a metal hydroxide such as aluminum hydroxide or magnesium hydroxide, and a thermally conductive filler. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-2425 [Patent Document 2] JP 2020-132843 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in both of the technologies of Patent Documents 1 and 2, the laminate film of the battery exterior absorbs heat, so the content of the heat absorbing material is limited due to the constraints of the thickness or flexibility of the film, and sufficient heat absorbing effect cannot be obtained. In addition, since the resin molding temperature used in Patent Document 2 generally requires 150°C or more, if calcium sulfate dihydrate is contained as the heat absorbing material, the endothermic reaction occurs from the endothermic start temperature of 120°C of the calcium sulfate dihydrate, making molding difficult. Therefore, in the technology of Patent Document 2, molding is performed at 80°C, but another problem occurs in that the strength is not sufficient for use as a battery exterior film alone. Furthermore, the technologies of Patent Documents 1 and 2 do not consider temperature control before thermal runaway, expansion of the battery cell, and flame insulation. Therefore, an object of the present disclosure is to provide a heat absorber that has a low heat absorption initiation temperature and is excellent in heat absorption amount, flame retardancy, and cushioning properties, and a secondary battery module including the heat absorber. [Means for solving the problem]
[0006] The present inventors have found that a heat absorber containing a bag and a hydrogel exhibits a low heat absorption onset temperature, and is excellent in heat absorption amount, flame retardancy and cushioning properties, and have completed the present invention. [1] A heat absorber having a bag that can be filled with a content and a hydrogel that is filled into the bag as the content. [2] The water vapor permeability ([g / (m 2 24h)] is 50g / (m 2 The heat endothermic material according to [1], wherein the heat endothermic effect is less than 24 h. [3] The heat sink according to [1] or [2], wherein the hydrogel is an organic-inorganic composite hydrogel. [4] The heat absorber according to any one of [1] to [3], wherein the hydrogel is prepared by using at least a water-soluble organic monomer and a water-swellable clay mineral as reaction raw materials. [5] The heat endothermic material according to any one of [1] to [4], further comprising a low-volatility solvent as the content. [6] The heat absorber according to any one of [1] to [5], which is used in a battery. [7] The heat absorber according to [6], wherein the battery is a secondary battery. [8] A secondary battery module comprising the heat absorber according to any one of [1] to [7]. [9] The secondary battery module according to [8], in which the heat absorber according to any one of [1] to [7] is sandwiched between battery cells.
[10] The secondary battery module according to [8] or [9], wherein the heat absorber according to any one of [1] to [7] has a total thickness in the range of 100 to 50,000 μm. Effect of the Invention
[0007] The heat absorber of the present disclosure has a low heat absorption onset temperature and is excellent in heat absorption amount, flame retardancy, and cushioning properties. According to the present disclosure, a highly safe secondary battery module can be provided by including a heat absorber that has a low heat absorption initiation temperature and is excellent in heat absorption amount, flame retardancy, and cushioning properties. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 shows an example of a secondary battery module in which the heat absorber of this embodiment can be mounted. [Diagram 2] FIG. 2 is a perspective view that illustrates a schematic exploded view of the secondary battery module of FIG. [Diagram 3] FIG. 3 shows the results of DSC measurement indicating the endothermic onset temperature and endothermic amount of the heat absorber in Example 1. [Figure 4] FIG. 4 shows the results of DSC measurement indicating the endothermic onset temperature and endothermic amount of the heat absorber in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Below, an embodiment of the present invention (hereinafter referred to as the "present embodiment") will be described in detail, but the present disclosure is not limited to the description below and can be implemented in various modifications within the scope of its gist. [Definition] The term "reaction raw material" as used herein refers to a compound that is used to obtain a target compound through a chemical reaction such as synthesis or decomposition and that partially constitutes the chemical structure of the target compound, and excludes substances that play the role of auxiliary agents in chemical reactions, such as solvents, catalysts, and polymerization initiators. The term "structural unit" as used herein refers to a (repeating) unit of a chemical structure formed during a reaction or polymerization; in other words, it refers to a partial structure other than the structure of the chemical bonds involved in the reaction or polymerization in a product compound formed during a reaction or polymerization, i.e., a so-called residue. In this specification, the term "hydrogel" refers to a three-dimensional network of polymers that contains an aqueous solvent such as water, and includes, for example, jelly, absorbent diapers, konjac, agar, etc. The three-dimensional network polymer that is the skeleton of the hydrogel is called the hydrogel body, and the hydrogel body contains an aqueous solvent. Thus, the hydrogel contains the hydrogel body and an aqueous solvent.
[0010] [Heat absorber] The heat absorber of the present disclosure (hereinafter, may be simply referred to as "heat absorber") is a heat absorber having a bag and a hydrogel filled in the bag. The hydrogel is not particularly limited, and known hydrogels can be used. For example, a hydrogel that holds an aqueous solvent in a three-dimensional mesh structure (three-dimensional network) whose main component is a polymer synthesized from water-soluble organic monomers or the like is preferred, and even more preferred is a hydrogel that holds an aqueous solvent in a three-dimensional mesh structure (three-dimensional network) whose main component is a polymer synthesized from water-soluble organic monomers in the presence of a water-swellable clay mineral. The content of the aqueous solvent in the hydrogel is in the range of 5 to 99% by mass relative to the entire hydrogel, and can exhibit a heat absorbing effect at a level capable of effectively preventing ignition or damage due to thermal runaway of the secondary battery, and is suitable as a heat absorber, particularly as a heat absorber for batteries, particularly as a heat absorber for secondary batteries. The upper limit of the content of the aqueous solvent in the hydrogel is preferably 99% by mass or less, more preferably 90% by mass or less, and even more preferably 80% by mass or less, relative to the entire gel. The lower limit of the content of the aqueous solvent is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more. The preferred range of the content of the aqueous solvent can be an appropriate combination of the upper and lower limits.
[0011] Specific examples of such hydrogels include organic-inorganic composite hydrogels (NC gels), interpenetrating network structure hydrogels (DN gels), slide-ring gels (SR gels), and hydrogels called aquamaterials. Of these, organic-inorganic composite hydrogels (also called organic-inorganic hydrogels or NC gels (nanocomposite gels)) are preferred because of their excellent heat absorbing performance due to the aqueous solvent contained therein, and because they have excellent cushioning properties and creep resistance.
[0012] The content of the hydrogel in this embodiment is preferably 100% by mass or less, more preferably 90% by mass or less, and preferably 20% by mass or more, more preferably 25% by mass or more, based on the entire heat absorber (total amount of the contents of the bag). The preferred range of the content of the hydrogel in the contents can be appropriately combined with the above upper and lower limits (the preferred range of the content can be, for example, 20% by mass to 100% by mass, or 25% by mass to 90% by mass).
[0013] This makes it possible to provide a heat absorber that has a low heat absorption start temperature and is excellent in flame retardancy, heat absorption amount, and cushioning properties. As a result, by providing the heat absorber, the heat absorption properties are exerted, and it is possible to provide a secondary battery module that is highly safe by suppressing the temperature effect on other battery cells. Furthermore, the heat absorber of the present disclosure has a strength that allows it to be used alone. Furthermore, if necessary, the pouch may be further filled with one or more types selected from the group consisting of low-volatility solvents and additives. The endothermic onset temperature of the heat absorber of this embodiment is preferably 160° C. or lower, more preferably 150° C. or lower, even more preferably 120° C. or lower, more preferably 110° C. or lower, and even more preferably 100° C. or lower. The lower limit of the endothermic onset temperature is not particularly limited, but is preferably 70° C. or higher, more preferably 80° C. or higher, and even more preferably 90° C. or higher. The upper and lower limits of the preferred range of the endothermic onset temperature can be appropriately combined (for example, the preferred range of the endothermic onset temperature can be 70° C. or higher and 160° C. or lower, 70° C. or higher and 150° C. or lower, 80° C. or higher and 120° C. or lower, or 90° C. or higher and 100° C. or lower). In this specification, the endothermic onset temperature (°C) is the temperature of the intersection of a straight line extending the low-temperature baseline to the high-temperature side in a DSC measurement curve, which is the measurement result of a differential scanning calorimeter (DSC), and a tangent drawn at the point where the gradient is maximum on the low-temperature side curve of the endothermic peak associated with evaporation. However, when multiple endothermic peaks are observed, the intersection of a straight line extending the low-temperature baseline to the high-temperature side and a tangent drawn at the point where the gradient is maximum on the low-temperature side curve of each of the multiple endothermic peaks is calculated for each of the multiple endothermic peaks, and the lowest temperature among the multiple intersections is taken as the endothermic onset temperature. The endothermic peak temperature of the heat absorber of this embodiment is preferably in the range of at least 80°C to 160°C, and more preferably in the range of 90°C to 150°C. In this specification, the endothermic peak temperature refers to the temperature (°C) at the maximum value of the endothermic peak due to evaporation in a DSC measurement curve, which is the measurement result of a differential scanning calorimeter (DSC). When multiple endothermic peaks are observed, at least one of the multiple endothermic peaks may be present in the range of 80°C to 160°C. The endothermic amount of the heat absorber of this embodiment is not particularly limited, but is preferably 100 J / g or more, more preferably 200 J / g or more, even more preferably 300 J / g or more, and even more preferably 500 J / g or more at the endothermic peak temperature (range of 80 ° C. to 160 ° C.), and is preferably in the range of 3000 J / g or less, more preferably 2500 J / g or less, and even more preferably 2000 J / g or less. The preferred range of the endothermic amount can be a combination of the upper and lower limits as appropriate (for example, the preferred range of the endothermic amount can be 100 J / g to 3000 J / g, 200 J / g to 2500 J / g, 300 J / g to 2000 J / g, or 500 J / g to 2000 J / g). The endothermic onset temperature, endothermic peak temperature and endothermic amount of the heat endotherm of the present embodiment are values determined using a differential scanning calorimeter (DSC) according to the method of the examples described below.
[0014] The shape or size of the heat absorber of this embodiment is not particularly limited, and may be, for example, substantially spherical, substantially flat, or amorphous, and is appropriately selected according to the size of the secondary battery to be used. For example, a substantially flat heat absorber is preferable because it is easy to install between adjacent battery cells. When the heat absorber of the present embodiment is substantially flat, the average thickness is not particularly limited, and may be, for example, in the range of 100 μm to 50,000 μm. The lower limit of the average thickness is preferably 100 μm or more, more preferably 200 μm or more, even more preferably 500 μm or more, and particularly preferably 1,000 μm or more. The upper limit of the average thickness is preferably 50,000 μm or less, more preferably 20,000 μm or less, even more preferably 10,000 μm or less, and particularly preferably 8,000 μm or less. The preferred range of the average thickness is a combination of the upper and lower limits as appropriate (the preferred range of the average thickness may be, for example, 200 μm to 20,000 μm, 500 μm to 10,000 μm, or 1,000 μm to 8,000 μm). Below, the essential components of the heat absorber of this embodiment, namely the bag and the hydrogel (including the aqueous solvent contained in the hydrogel), and the optional components such as the low-volatility solvent and additives that are blended as necessary will be described.
[0015] (Bag body) The bag of the present embodiment is not particularly limited as long as the contents, that is, the hydrogel or the aqueous solvent, do not leak out to the outside. As the bag, for example, a three-sided bag having an opening on the upper end side, a body part whose lower end is closed, and a structure in which the opening is heat-sealed so as to be closed after the contents, that is, the hydrogel and the aqueous solvent, are contained therein is preferable. The three-sided bag is constructed by gluing together the lower ends and side portions of two sheets and sealing them after the contents are filled in through the opening, so that it has excellent airtightness, and its approximately flat shape makes it easy to insert between battery cells. The bag body of this embodiment is preferably made of a sheet. In addition, as a preferred embodiment of the bag body of this embodiment, two sheets of film of a desired size and shape (for example, rectangular or (approximately) circular) are stacked according to the purpose of use, and a predetermined heat-sealed area (for example, the edge of the film) is heat-pressurized to form an opening, thereby bonding the heat-sealed area. This forms an internal space area that can be filled with the contents, and has an opening so that the contents can be filled into the internal space area through the opening, and a three-sided bag in which the heat-sealed areas of the two sheets are bonded together can be produced. Then, after filling the contents, the openings can be heat-sealed by pressing them together. In this specification, the term "sealed" refers to a state in which the inside and outside of the bag are substantially sealed off. For example, as long as the contents do not leak out, the permeation of a small amount of gas such as water vapor is permitted. The sheet used in the bag body of this embodiment is not particularly limited as long as it exhibits water impermeability, and examples thereof include known resin films, resin films having a metal layer, and films having a metal layer. The average thickness of the sheet used in the bag of this embodiment is not particularly limited, but is preferably 30 μm to 200 μm, and more preferably 60 μm to 150 μm. Examples of materials for the resin film include one or more resins such as polyester resin, nylon resin, polycarbonate resin, polypropylene resin, polyethylene resin, cyclic polyolefin resin, polystyrene resin, fluororesin, and elastomer. These plastics can be used for the bag as a film, sheet, tube, etc. In addition, the resin film having the metal layer may be laminated on the resin film as a metal foil, a vapor deposition film, or the like, of a metal such as aluminum, or a metal oxide such as silica or alumina. By using a resin film having a metal layer, the water vapor permeability of the resin film can be reduced. In addition, the water vapor permeability of the sheet can be adjusted by the selection, thickness, combination, or the like of materials. Examples of the lamination method include dry lamination, extrusion lamination, heat lamination, coextrusion, multilayer blow molding, laminate injection molding, coating, and the like. In addition, a preferred form of the resin film having a metal layer is an aluminum laminate film (a film in which an aluminum foil (including an aluminum vapor deposition layer) and a thermoplastic resin film (for example, a polyethylene film, a PP film, a PET film) laminated on at least one surface of the aluminum foil are integrated). In this embodiment, an adhesive layer may be formed in the heat seal area and the opening to be closed for the purpose of sealing. As the adhesive layer, for example, a laminate adhesive such as a polyester adhesive, a polyether adhesive, or a polyurethane adhesive can be suitably used. Furthermore, the nature of the adhesive is not particularly limited, and for example, any of a solvent type, a solventless type, and a water-based type can be used. For example, in the present invention, a bag body formed by sealing a resin film having an aluminum-deposited layer on the outside via a polyurethane-based laminate adhesive layer can be suitably used. For example, gas barrier aluminum bag AB series (manufactured by Mitsubishi Gas Chemical Company, Inc.) and Lamizip AL type (manufactured by Seisan Nippon Co., Ltd.) can be mentioned. The higher the melting temperature (for example, 120 to 140° C.) of the adhesive used to close the opening of the bag of this embodiment or applied to the heat-sealed area, the higher the strength and the more likely it is to withstand internal pressure.
[0016] The water vapor permeability ([g / (m 2 24h)] is 50g / (m 2 24h) or less, and 10g / (m 2 24h) or less is more preferable, and 5g / (m 2It is even more preferable that the time is 24 hours or less. The water vapor permeability of the sheet that makes up the bag is 50g / (m 2 If the storage time is within the range of 24 hours or less, the moisture inside the bag can be prevented from leaking out to the outside, which is preferable from the viewpoint of preventing deterioration of the heat absorbing performance over time. The water vapor permeability ([g / (m 2 The lower limit of the β-g / (m 24h) is not particularly limited, but is preferably 0 g / (m 2 ·24h) or more, and more preferably 0g / (m 2 The preferred range of water vapor permeability may be, for example, 0 g / (m 2 ·24h) or more 50g / (m 2 24h) or less, or 0g / (m 2 ·24h) or more 10g / (m 2 From another viewpoint, the preferable range of the water vapor permeability is 0 g / (m 2 ·24h) Super 50g / (m 2 -24h) or less. The water vapor permeability ([g / (m 2 24h) is measured in accordance with the JIS K7129 standard at a temperature of 40°C and a relative humidity of 90%.
[0017] (Hydrogel) The hydrogel of this embodiment preferably has an aqueous solvent and a three-dimensional polymeric network structure that retains the aqueous solvent therein, and has an aqueous solvent and a hydrogel body that is a three-dimensional polymeric network structure that includes a water-swellable clay mineral and a water-soluble organic monomer structural unit, at least a portion of which is dissolved or dispersed in the aqueous solvent. Examples of the hydrogel include an interpenetrating network gel in which two types of acrylic polymers each form a three-dimensional network structure, a slide-ring gel in which cyclodextrin forms the skeleton of the three-dimensional network structure, and an aqua material in which a multi-branched dendrimer forms the main skeleton of the three-dimensional network structure and a water-swellable clay mineral is added. In this disclosure, the following will be described based on an organic-inorganic composite hydrogel, which is one aspect of this embodiment. The organic-inorganic composite hydrogel of this embodiment has a three-dimensional network structure containing a water-soluble organic monomer structural unit and a water-swellable clay mineral as the hydrogel body. More specifically, the hydrogel body of the organic-inorganic composite hydrogel (hereinafter also referred to as the organic-inorganic composite hydrogel body) is considered to be a polymer gel (= three-dimensional network structure) in which polymer chains composed of a plurality of water-soluble organic monomer structural units are crosslinked via a water-swellable clay mineral that functions as a binding point, and the organic-inorganic composite hydrogel can swell by taking in an aqueous solvent such as water into the three-dimensional network structure of the polymer gel. As a result, the swollen organic-inorganic composite hydrogel not only has heat absorption capabilities and exhibits excellent cushioning properties that accommodate relatively short-term deformations such as expansion and contraction due to charging and discharging of the battery cell, but also exhibits excellent creep resistance that can relieve internal pressure caused by expansion of the battery cell over time. The organic-inorganic composite hydrogel preferably has a three-dimensional network structure and is made from water-soluble organic monomers and water-swellable clay minerals as reaction raw materials.
[0018] The organic-inorganic composite hydrogel according to one aspect of the present embodiment is produced by using at least a water-soluble organic monomer structural unit and a water-swellable clay mineral as reaction raw materials. As a method for producing the organic-inorganic composite hydrogel according to one aspect of the present embodiment, a method of polymerizing the water-soluble organic monomer in a dispersion liquid (a) containing a water-soluble organic monomer, a water-swellable clay mineral, an aqueous solvent, and, if necessary, a polymerization initiator and an additive, is preferred, since this method allows an organic-inorganic composite hydrogel having a three-dimensional network structure to be easily obtained. The obtained polymer of the water-soluble organic monomer forms a three-dimensional network structure together with the water-swellable clay mineral, and becomes a component of the organic-inorganic composite hydrogel.
[0019] The lower limit of the content of the hydrogel body according to this embodiment may be preferably 1% by mass or more, more preferably 10% by mass or more, based on the total amount of the hydrogel. On the other hand, the upper limit of the content of the hydrogel body may be preferably 50% by mass or less, more preferably 40% by mass or less. The preferred range of the content of the hydrogel body may be an appropriate combination of the upper and lower limits (the preferred range of the content may be, for example, 1% by mass to 50% by mass, or 10% by mass to 40% by mass). For example, when the hydrogel body is composed of a water-soluble organic monomer structural unit described below, the content of the hydrogel body may be the total amount of the water-soluble organic monomer structural unit and the water-swellable clay mineral. The content of the hydrogel body was calculated based on the mass change (%) before and after drying the hydrogel at 120° C. for 2 hours.
[0020] <Water-soluble organic monomer> The water-soluble organic monomer used in this embodiment constitutes the organic-inorganic composite hydrogel body as the water-soluble organic monomer structural unit. The lower limit of the content of the water-soluble organic monomer structural unit in the hydrogel according to this embodiment may be preferably 0.9% by mass or more, more preferably 1% by mass or more, and even more preferably 5% by mass or more, based on the total amount of the hydrogel. Meanwhile, the upper limit of the content of the water-soluble organic monomer structural unit may be 50% by mass or less, 40% by mass or less, or 30% by mass or less. The preferred range of the content of the water-soluble organic monomer structural unit in the hydrogel may be an appropriate combination of the above upper and lower limits (the preferred range of the content may be, for example, 0.9% by mass to 50% by mass, 1% by mass to 40% by mass, or 5% by mass to 30% by mass). The type of water-soluble organic monomer used in the present embodiment is not particularly limited, but examples thereof include monomers having a (meth)acrylamide group, monomers having a (meth)acryloyloxy group, and acrylic monomers having a hydroxyl group. In this specification, "(meth)acrylamide" refers to either or both of acrylamide and methacrylamide, "(meth)acryloyloxy" refers to either or both of acryloyloxy and (meth)acryloyloxy, "(meth)acrylate" refers to either or both of acrylate and methacrylate, and "(meth)acrylic monomer" refers to either or both of acrylic monomer and methacrylic monomer.
[0021] Examples of the monomer having a (meth)acrylamide group include acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, N-methylacrylamide, N-ethylacrylamide, N-isopropylacrylamide, N-cyclopropylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-diethylaminopropylacrylamide, acryloylmorpholine, methacrylamide, N,N-dimethylmethacrylamide, N,N-diethylmethacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, N-isopropylmethacrylamide, N-cyclopropylmethacrylamide, N,N-dimethylaminopropylmethacrylamide, and N,N-diethylaminopropylmethacrylamide. Preferred examples of the monomer having a (meth)acrylamide group include acrylamide, N,N-dimethylacrylamide, N-methylacrylamide, N-ethylacrylamide, acryloylmorpholine, methacrylamide, N,N-dimethylmethacrylamide, N-methylmethacrylamide, and N-ethylmethacrylamide.
[0022] Examples of the monomer having a (meth)acryloyloxy group include methoxyethyl acrylate, ethoxyethyl acrylate, methoxyethyl methacrylate, ethoxyethyl methacrylate, methoxymethyl acrylate, and ethoxymethyl acrylate.
[0023] Examples of the acrylic monomer having a hydroxyl group include hydroxyethyl acrylate, hydroxyethyl methacrylate, etc. As the water-soluble organic monomer used in the present embodiment, the acrylic monomer having a hydroxyl group may be used alone or in combination of two or more kinds.
[0024] In this embodiment, when a homopolymer is obtained from a water-soluble organic monomer, the resulting homopolymer preferably has a lower critical solution temperature (°C) of 50°C or higher, more preferably 60°C or higher, and preferably does not have a lower critical solution temperature (°C), i.e., the lower critical solution temperature (°C) cannot be observed in an aqueous solvent. As a result, the polymer chains made of water-soluble organic monomer structural units that constitute the organic-inorganic composite hydrogel do not undergo phase transition at temperatures below 50°C, making it possible to achieve both excellent cushioning properties and heat absorption capabilities even at high temperatures. More specifically, the organic-inorganic composite hydrogel according to one aspect of the present embodiment has, as a constituent component, a polymer chain composed of a water-soluble organic monomer structural unit obtained by polymerization or reaction of a water-soluble organic monomer. Therefore, when the temperature reaches or exceeds the lower critical solution temperature (°C) of the polymer chain composed of the water-soluble organic monomer structural unit, the polymer chain undergoes a phase transition due to desolvation, and is separated into a phase containing the polymer chain and a phase containing an aqueous solvent. As a result, the three-dimensional network structure of the organic-inorganic composite hydrogel containing the aqueous solvent cannot be maintained, and it becomes difficult to exhibit cushioning properties. Therefore, the lower critical solution temperature (°C) of the organic-inorganic composite hydrogel in an aqueous solvent is preferably 50°C or higher, more preferably 60°C or higher, and it is preferable that the organic-inorganic composite hydrogel does not have a lower critical solution temperature (°C), i.e., the lower critical solution temperature (°C) cannot be observed in an aqueous solvent.
[0025] From the viewpoint of suppressing the phase transition of the organic-inorganic composite hydrogel, the water-soluble organic monomer used in the present embodiment is preferably a water-soluble organic monomer having a repeating unit in a homopolymer that does not have a lower critical solution temperature in an aqueous solvent, specifically, (meth)acrylamide, N,N-dimethyl(meth)acrylamide, acryloylmorpholine, methoxyethyl acrylate, ethoxyethyl acrylate, methoxyethyl methacrylate, ethoxyethyl methacrylate, methoxymethyl acrylate, ethoxymethyl acrylate, hydroxyethyl acrylate, or hydroxyethyl methacrylate. When an organic-inorganic composite hydrogel is heated to a temperature equal to or higher than the lower critical solution temperature (°C) of the organic-inorganic composite hydrogel or the polymer chains constituting the organic-inorganic composite hydrogel, the organic-inorganic composite hydrogel undergoes a phase transition and is separated into a phase in which the polymer chains containing the water-soluble organic monomer structural units constituting the organic-inorganic composite hydrogel are aggregated, and a phase of the aqueous solvent contained in the organic-inorganic composite hydrogel. Therefore, it is particularly preferable that the polymer chains constituting the organic-inorganic composite hydrogel do not have a lower critical solution temperature in the aqueous solvent. Therefore, a water-soluble organic monomer capable of forming a highly hydrophilic polymer chain is preferable. Furthermore, when the polymer chains constituting the organic-inorganic composite hydrogel are composed of two or more water-soluble organic monomers, from the viewpoint of reducing the decrease in cushioning property or liquid leakage due to phase transition, the lower critical solution temperature (°C) of the copolymer composed of the two or more water-soluble organic monomers is preferably 50°C or higher, more preferably 60°C or higher, and preferably does not have a lower critical solution temperature (°C), i.e., the lower critical solution temperature (°C) cannot be observed in an aqueous solvent.
[0026] Furthermore, among the above water-soluble organic monomers, from the viewpoints of solubility and cushioning properties of the resulting organic-inorganic composite hydrogel, it is preferable to use a monomer having a (meth)acrylamide group, it is more preferable to use acrylamide, N,N-dimethylacrylamide, or acryloylmorpholine, it is even more preferable to use N,N-dimethylacrylamide or acryloylmorpholine, and from the viewpoint of easy polymerization, N,N-dimethylacrylamide is particularly preferable. The above-mentioned water-soluble organic monomers may be used alone or in combination of two or more kinds.
[0027] <Water-swellable clay minerals> The water-swellable clay mineral used in this embodiment forms a three-dimensional network structure together with the polymer chain having the above-mentioned water-soluble organic monomer structural unit (polymer having a water-soluble organic monomer structural unit), and becomes a component of the organic-inorganic composite hydrogel and the organic-inorganic composite hydrogel body. The water-swellable clay mineral used in the present embodiment is not particularly limited, and examples thereof include water-swellable smectite, water-swellable mica, etc. Examples of the water-swellable smectite include water-swellable hectorite, water-swellable montmorillonite, water-swellable saponite, etc. Examples of the water-swellable mica include water-swellable synthetic mica, etc. Among these, from the viewpoint of dispersibility, it is preferable to use water-swellable hectorite and water-swellable montmorillonite, and it is more preferable to use water-swellable hectorite.
[0028] The water-swellable clay mineral used in the present embodiment may be a natural clay mineral, a synthetic clay mineral, or a clay mineral whose surface has been modified. Examples of the water-swellable clay mineral whose surface has been modified include phosphonic acid-modified hectorite and fluorine-modified hectorite. From the viewpoint of the heat absorption and cushioning properties of the resulting organic-inorganic composite hydrogel, it is preferable to use phosphonic acid-modified hectorite. The above-mentioned water-swellable clay minerals may be used alone or in combination of two or more kinds.
[0029] The phosphonic acid modified hectorite forms a three-dimensional network structure together with the polymer of the water-soluble organic monomer, and becomes a component of the organic-inorganic composite hydrogel. As the phosphonic acid modified hectorite, for example, pyrophosphoric acid modified hectorite, etidronic acid modified hectorite, alendronic acid modified hectorite, methylenediphosphonic acid modified hectorite, phytic acid modified hectorite, etc. can be used. These phosphonic acid modified hectorites can be used alone or in combination of two or more. The content of the water-swellable clay mineral in this embodiment is preferably 50% by mass or less, more preferably 30% by mass or less, even more preferably 20% by mass or less, and particularly preferably 10% by mass or less, based on the total amount of the polymer derived from the water-soluble organic monomer contained in the organic-inorganic composite hydrogel, the water-swellable clay mineral, the polymerization initiator, and the aqueous solvent. The lower limit of the content of the water-swellable clay mineral is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 2% by mass or more, and particularly preferably 3% by mass or more. The upper and lower limits of the content of the water-swellable clay mineral in the organic-inorganic composite hydrogel can be appropriately combined (for example, the content can be preferably in the range of 0.1% by mass to 50% by mass, 1% by mass to 30% by mass, 2% by mass to 20% by mass, or 3% by mass to 10% by mass).
[0030] <Reaction materials> In one aspect of this embodiment, the heat absorber contains a bag and an organic-inorganic composite hydrogel as the content of the bag. The organic-inorganic composite hydrogel, which is one aspect of this embodiment, uses at least a water-swellable clay mineral and a water-soluble organic monomer as reaction raw materials. In this case, the organic-inorganic composite hydrogel may be filled into the bag as a gel and then the bag may be sealed, or the water-soluble organic monomer and the water-swellable clay mineral, which are reaction raw materials of the organic-inorganic composite hydrogel, may be filled into the bag together with an aqueous solvent (an organic solvent and a polymerization initiator may be added as necessary), and then the water-soluble organic monomer and the water-swellable clay mineral inside the bag may be gelled while the bag is sealed.
[0031] As a method for producing the organic-inorganic composite hydrogel, which is one aspect of this embodiment, a method in which the water-soluble organic monomer is polymerized in a dispersion liquid (a) containing the water-soluble organic monomer and the water-swellable clay mineral as reaction raw materials, a polymerization initiator, and an aqueous solvent is preferred, because the organic-inorganic composite hydrogel can be easily obtained. The content of the water-soluble organic monomer in the dispersion (a) is, for example, in the range of 0.9% by mass to 50% by mass based on the total amount (mass) of the water-soluble organic monomer, the water-swellable clay mineral, and the aqueous solvent. The lower limit of the content of the water-soluble organic monomer is preferably 0.9% by mass or more, more preferably 1% by mass or more, and even more preferably 5% by mass or more. The upper limit of the content of the water-soluble organic monomer is preferably 50% by mass or less, and more preferably 30% by mass or less. The upper and lower limits of the content can be appropriately combined. It is preferable that the content of the water-soluble organic monomer is 0.9% by mass or more, since a hydrogel having excellent mechanical properties can be obtained. On the other hand, it is preferable that the content of the water-soluble organic monomer is 50% by mass or less, since the dispersion can be easily prepared. The content of the water-swellable clay mineral in the dispersion (a) is, for example, in the range of 0.1% by mass to 50% by mass based on the total amount (mass) of the water-soluble organic monomer, the water-swellable clay mineral, and the aqueous solvent. The lower limit of the content of the water-swellable clay mineral is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 3% by mass or more. The upper limit of the content of the water-swellable clay mineral is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 10% by mass or less. The upper and lower limits of the content can be appropriately combined (for example, the content can be in the range of 1% by mass to 30% by mass, or in the range of 3% by mass to 10% by mass). When the content of the water-swellable clay mineral is 0.1% by mass or more, the mechanical properties of the obtained hydrogel are further improved, which is preferable. On the other hand, when the content of the water-swellable clay mineral is 50% by mass or less, the increase in the viscosity of the dispersion (a) can be further suppressed, which is preferable. The dispersion (a) has better storage stability by using phosphonic acid-modified hectorite as the water-swellable clay mineral, but may contain other water-swellable clay minerals as long as the storage stability is not impaired. The content of the aqueous solvent in the dispersion (a) is, for example, in the range of 50% by mass to 99% by mass based on the total amount (mass) of the water-soluble organic monomer, the water-swellable clay mineral, and the aqueous solvent. The lower limit of the aqueous solvent content is preferably 50% by mass or more, more preferably 60% by mass or more. The upper limit of the aqueous solvent content is preferably 99% by mass or less, more preferably 90% by mass or less. The upper and lower limits of the content can be appropriately combined (for example, the content can be in the range of 50% by mass to 90% by mass, or in the range of 60% by mass to 90% by mass). It is preferable that the content of the aqueous solvent is 90% by mass or less, because a hydrogel having excellent mechanical properties can be obtained. On the other hand, it is preferable that the content of the aqueous solvent is 60% by mass or more, because it is easy to prepare the dispersion (a) in which each component is uniformly dispersed. In addition, in addition to the reaction raw materials, that is, the water-soluble organic monomer and the water-swellable clay mineral, the polymerization initiator, and the aqueous solvent, the dispersion liquid (a) may contain one or more selected from the group consisting of the low-volatility solvents and additives described below.
[0032] The dispersion liquid (a) of the present embodiment preferably contains a polymerization initiator. The polymerization initiator is not particularly limited, but may be a water-soluble peroxide, a water-soluble azo compound, or the like.
[0033] Examples of the water-soluble peroxide include potassium peroxodisulfate, ammonium peroxodisulfate, sodium peroxodisulfate, and t-butyl hydroperoxide. Examples of the water-soluble azo compound include 2,2'-azobis(2-methylpropionamidine) dihydrochloride and 4,4'-azobis(4-cyanovaleric acid). Among these, from the viewpoint of interaction with water-swellable clay minerals, it is preferable to use water-soluble peroxides, more preferably potassium peroxodisulfate, ammonium peroxodisulfate, or sodium peroxodisulfate, and even more preferably sodium peroxodisulfate or ammonium peroxodisulfate. The above-mentioned polymerization initiators may be used alone or in combination of two or more kinds.
[0034] In one aspect of the present embodiment, the polymerization initiator is not essential, but when used, the molar ratio of the polymerization initiator to the water-soluble organic monomer in the dispersion liquid (a) (polymerization initiator / water-soluble organic monomer) is preferably 0.01 or more, more preferably 0.02 to 0.1, and even more preferably 0.04 to 0.1.
[0035] The content of the polymerization initiator in the dispersion (a) is not essential, but when used, it is preferably 0.1% by mass to 10% by mass, more preferably 0.2% by mass to 5% by mass, based on the total amount (mass) of the water-soluble organic monomer, the water-swellable clay mineral, the aqueous solvent, and the polymerization initiator. If the content of the polymerization initiator is 0.1% by mass or more, it is preferable because the polymerization of the water-soluble organic monomer is possible even in an air atmosphere. On the other hand, if the content of the polymerization initiator is 10% by mass or less, it is preferable because the dispersion can be used without flocculation before polymerization, and the handling is improved.
[0036] The dispersion liquid (a) contains a water-soluble organic monomer, a water-swellable clay mineral, and an aqueous solvent, and may further contain an organic solvent, a catalyst, an organic crosslinking agent, a preservative, a thickener, etc., as necessary. Examples of the organic solvent include alcohol compounds such as methanol, ethanol, propanol, isopropyl alcohol, and 1-butanol; ether compounds such as ethyl ether and ethylene glycol monoethyl ether; amide compounds such as dimethylformamide and N-methylpyrrolidone; and ketone compounds such as acetone and methyl ethyl ketone. Among these, from the viewpoint of dispersibility of the water-swellable clay mineral, it is preferable to use an alcohol compound, more preferably methanol, ethanol, n-propyl alcohol, or isopropyl alcohol, and even more preferably methanol or ethanol. These organic solvents may be used alone or in combination of two or more kinds.
[0037] The catalyst has the function of increasing the polymerization rate when the water-soluble organic monomer is polymerized. The catalyst is not particularly limited, but examples thereof include tertiary amine compounds, thiosulfates, ascorbic acids, and the like. Examples of the tertiary amine compound include N,N,N',N'-tetramethylethylenediamine, 3-dimethylaminopropionitrile, and the like. Examples of the thiosulfates include sodium thiosulfate and ammonium thiosulfate. Examples of the ascorbic acids include L-ascorbic acid and sodium L-ascorbate. Among these, from the viewpoint of the stability of the dispersion liquid, it is preferable to use a tertiary amine compound, and it is more preferable to use N,N,N',N'-tetramethylethylenediamine. The above catalysts may be used alone or in combination of two or more kinds. Although a catalyst is not essential, when a catalyst is used, the content of the catalyst in the dispersion (a) is preferably 0.01% by mass to 1% by mass, more preferably 0.05% by mass to 0.5% by mass, based on the total amount (mass) of the water-soluble organic monomer, the water-swellable clay mineral, the aqueous solvent, and the catalyst. If the content of the catalyst is 0.01% by mass or more, the synthesis of the hydrogel obtained from the water-soluble organic monomer can be efficiently promoted, which is preferable. On the other hand, if the content of the catalyst is 1% by mass or less, the dispersion can be used without flocculation before polymerization, which improves the handleability.
[0038] Examples of methods for preparing the dispersion liquid (a) include a method in which a water-soluble organic monomer, a water-swellable clay mineral, a polymerization initiator, an aqueous solvent such as water, and the like are mixed together at once; and a multi-liquid mixing method in which a dispersion liquid (a1) containing a water-soluble organic monomer and a solution (a2) containing a polymerization initiator are prepared as separate dispersions or solutions and mixed immediately before use. From the viewpoints of dispersibility, storage stability, viscosity control, and the like, the multi-liquid mixing method is preferred.
[0039] The dispersion (a1) containing the water-soluble organic monomer may, for example, be a dispersion in which a water-soluble organic monomer and a water-swellable clay mineral are mixed.
[0040] The solution (a2) containing a polymerization initiator may be, for example, an aqueous solution obtained by mixing a polymerization initiator with water.
[0041] The organic-inorganic composite hydrogel is obtained by polymerizing a water-soluble organic monomer in the dispersion liquid (a), and the polymerization method is not particularly limited and can be performed by a known method. Specifically, radical polymerization by heating or ultraviolet irradiation, radical polymerization using a redox reaction, etc. can be mentioned.
[0042] The polymerization temperature for polymerizing the organic-inorganic composite hydrogel is preferably 10° C. to 80° C., and more preferably 20° C. to 80° C. A polymerization temperature of 10° C. or higher is preferable because the radical reaction can proceed in a chain reaction. On the other hand, a polymerization temperature of 80° C. or lower is preferable because the water contained in the dispersion liquid (a) can be polymerized without boiling. The polymerization time of the organic-inorganic composite hydrogel varies depending on the type of polymerization initiator and catalyst, but is carried out between several tens of seconds and 24 hours. In particular, in the case of radical polymerization using heating or redox, the polymerization time is preferably 1 hour to 24 hours, and more preferably 5 hours to 24 hours. A polymerization time of 1 hour or more is preferable because the polymer of the water-swellable clay mineral and the water-soluble organic monomer can form a three-dimensional network structure. On the other hand, since the polymerization reaction is almost completed within 24 hours, the polymerization time is preferably 24 hours or less.
[0043] (Water-based solvent) The heat absorber of the present embodiment contains an aqueous solvent as its content. The aqueous solvent is preferably present mainly in the hydrogel, for example, the organic-inorganic composite hydrogel. The aqueous solvent of the present embodiment may contain water as the main component, and refers to water or a solvent containing water as the main component. Therefore, the aqueous solvent includes a mixed solvent with a solvent other than water, or an aqueous solution containing a salt (e.g., a buffer solution, an electrolyte solution). In this specification, "containing water as the main component" means that the aqueous solvent contains 45 mass% or more of water based on the entire aqueous solvent. In addition, the water can be purified water, pure water, ultrapure water, distilled water, or the like, without any particular limitation. Examples of the salt include alkali metal halides such as sodium chloride or potassium chloride, alkaline earth metal halides such as magnesium chloride or calcium chloride, and salts having buffering capacity such as tris-hydrochloric acid, glycine hydrochloride, citric acid-sodium citrate, acetic acid-sodium acetate, citric acid-disodium hydrogen phosphate, sodium dihydrogen phosphate-disodium hydrogen phosphate, glycine-sodium hydroxide, sodium carbonate-sodium hydrogen carbonate, etc. Furthermore, Good's buffers such as HEPES or MOPS may be used as the aqueous solvent. The solvent other than water constituting the mixed solvent includes organic solvents that are uniformly miscible with water (for example, lower alcohols, lower ketones, etc.). The upper limit of the water content in the aqueous solvent of this embodiment is preferably 100% by mass or less, more preferably 99% by mass or less, even more preferably 90% by mass or less, and particularly preferably 80% by mass or less, based on the total amount of the aqueous solvent. The lower limit of the water content is preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 20% by mass or more, and particularly preferably 45% by mass or more. The preferred range of the water content in the aqueous solvent can be an appropriate combination of the upper and lower limits (the preferred range of the water content can be, for example, 5% by mass to 100% by mass, 10% by mass to 99% by mass, 20% by mass to 90% by mass, or 45% by mass to 80% by mass).
[0044] (low volatility solvent) In this embodiment, a low volatility solvent can be used as an optional component because it is possible to balance the heat absorption performance and the cushioning property. In particular, by adding a low volatility solvent to the content of the heat absorber, it is possible to maintain high cushioning property over a wide temperature range. The low volatility solvent of the present embodiment has a volatility of 1 cm in an open system at 60° C. and 1 atm. 2 Less than 0.1g per hour (0.1g / cm 2Preferably, the organic solvent is used in an amount of 0.05 g or less, and more preferably 0.01 g or less. Specifically, a solvent that is easily miscible with water is preferred, and therefore glycerin (0.001 g or less / cm 2 ·hr·60℃·1atm), diglycerin (0.001g / cm 2 ·hr·60℃·1atm), ethylene glycol (0.01g / cm 2 ·hr·60℃·1atm), propylene glycol (0.001g or less / cm 2 ·hr·60℃·1atm), polyethylene glycol (0.001g / cm 2 Polyhydric alcohols such as glycerin, diglycerin, etc. are preferred, and glycerin and diglycerin are more preferred. These low-volatile solvents may be used alone or in combination of two or more. It is also preferred that these low-volatile solvents are uniformly contained in the organic-inorganic composite hydrogel. The heat endothermic material of this embodiment contains a low-volatility solvent, particularly a polyhydric alcohol, which suppresses or prevents the evaporation of the aqueous solvent, or suppresses a decrease in cushioning properties at low temperatures (improves the anti-freezing effect). When a low-volatility solvent is used as an optional component, the mass ratio of the aqueous solvent to the low-volatility solvent (aqueous solvent / low-volatility solvent) in the content of the heat absorber of this embodiment is preferably 60 / 40 to 20 / 80, and more preferably 50 / 50 to 30 / 70, since an organic-inorganic composite hydrogel having excellent heat absorption performance and various physical properties such as cushioning properties over a wide temperature range can be obtained.
[0045] (Additives) The contents or dispersion (a) of the heat absorber of this embodiment may contain various additives such as ultraviolet absorbers, antioxidants, organic solvents, inorganic fillers other than the water-swellable clay minerals, viscosity modifiers such as thickeners, crosslinking agents, and flame retardants, as necessary. Although the various additives are optional components, when they are used, it is preferable to use them in a ratio that does not impair the effects of the present invention and that corresponds to the purpose of each additive. Although the ratio cannot be determined in general, the content of the various additives is preferably 0% by mass or more, more preferably 10% by mass or more, based on the total amount (mass) of the hydrogel and various additives used in the present disclosure. In addition, it is preferably 50% by mass or less, more preferably 40% by mass or less.
[0046] Examples of the ultraviolet absorbent include triazine derivatives such as 2-[4-{(2-hydroxy-3-dodecyloxypropyl)oxy}-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-{(2-hydroxy-3-tridecyloxypropyl)oxy}-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, 2-(2'-xanthenecarboxy-5'-methylphenyl)benzotriazole, 2-(2'-o-nitrobenzyloxy-5'-methylphenyl)benzotriazole, 2-xanthenecarboxy-4-dodecyloxybenzophenone, and 2-o-nitrobenzyloxy-4-dodecyloxybenzophenone. These ultraviolet absorbents can be used alone or in combination of two or more.
[0047] Examples of the antioxidant include "Sumilizer BBM-S" and "Sumilizer GA-80" manufactured by Sumitomo Chemical Co., Ltd. Examples of the organic solvent include aromatic hydrocarbons such as toluene and xylene, glycols such as ethylene glycol and propylene glycol, polyether glycols which are polymers thereof, cellosolves, carbitols, aliphatic alcohols such as methanol, etc. The organic solvents can be used alone or in combination of two or more kinds. Examples of the inorganic filler include fused silica, crystalline silica, alumina, silicon nitride, and aluminum hydroxide. Examples of the viscosity adjuster such as the thickener include various tackifying resins such as rosin-based, polymerized rosin-based, polymerized rosin ester-based, rosin phenol-based, stabilized rosin ester-based, disproportionated rosin ester-based, terpene-based, terpene phenol-based oils, and petroleum resin-based tackifier resins. Examples of the crosslinking agent include known crosslinking agents such as isocyanate-based, epoxy-based, aziridine-based, polyvalent metal salt-based, metal chelate-based, ketohydrazide-based, oxazoline-based, carbodiimide-based, silane-based, and glycidyl (alkoxy) epoxy silane-based crosslinking agents.
[0048] Examples of the flame retardant include inorganic phosphorus compounds such as red phosphorus, ammonium phosphates such as monoammonium phosphate, diammonium phosphate, triammonium phosphate, and ammonium polyphosphate, and phosphoric acid amides; phosphoric acid ester compounds, phosphonic acid compounds, phosphinic acid compounds, phosphine oxide compounds, phosphorane compounds, organic nitrogen-containing phosphorus compounds, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxy, and the like. Examples of the flame retardant include organic phosphorus compounds such as cyclic organic phosphorus compounds such as 10-(2,7-dihydroxynaphthyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide and derivatives thereof reacted with compounds such as epoxy resins and phenolic resins; nitrogen-based flame retardants such as triazine compounds, cyanuric acid compounds, isocyanuric acid compounds, and phenothiazine; silicone-based flame retardants such as silicone oil, silicone rubber, and silicone resin; and inorganic flame retardants such as metal hydroxides, metal oxides, metal carbonate compounds, metal powders, boron compounds, and low-melting glass. These flame retardants can be used alone or in combination of two or more. In addition, when these flame retardants are used, the amount is preferably in the range of 0.1% by mass to 20% by mass with respect to the entire contents of the heat absorber or the entire dispersion liquid (a).
[0049] (Method of manufacturing heat absorber) In one aspect of this embodiment, the method for producing a heat absorber includes, as described above, a step of preparing dispersion liquid (a) containing reaction raw materials, i.e., a water-soluble organic monomer and a water-swellable clay mineral, an aqueous solvent, and optionally a polymerization initiator, a catalyst, a low-volatile solvent, and / or an additive; a step of filling an opening of a bag with the dispersion liquid (a), followed by sealing the bag; and a step of gelling the water-soluble organic monomer in the bag at a desired polymerization temperature. In addition, in one aspect of this embodiment, another method for producing a heat absorber includes the steps of preparing a mixed solution by mixing reaction raw materials, i.e., a water-soluble organic monomer and a water-swellable clay mineral, a polymerization initiator, and an aqueous solvent or an organic solvent; heating and gelling the mixed solution to prepare an organic-inorganic composite hydrogel body; immersing the organic-inorganic composite hydrogel body in the aqueous solvent for a desired period of time to cause the organic-inorganic composite hydrogel to swell in the aqueous solvent; and filling an opening of a bag with the swollen organic-inorganic composite hydrogel, followed by sealing. In the method for producing a heat absorber of this embodiment, even if a heat absorbing agent is mixed into the content of the heat absorber, the heat absorber can be molded at a molding temperature of 120°C by the above method.
[0050] (Use of heat absorber) As described above, the heat absorber of the present embodiment can exhibit a heat absorbing effect at a level that can effectively prevent ignition or damage due to thermal runaway of the secondary battery, and therefore can be suitably used for battery applications, particularly secondary battery applications. In addition, the application of the heat absorber of the present embodiment is not limited to battery applications, and can be used in general applications where prevention of fire spread is required. For example, the heat absorber of the present embodiment can be used together with building materials such as ceilings, walls, and kitchen surroundings.
[0051] [Secondary battery module] The type of secondary battery that can be equipped with the heat absorber of this embodiment is not particularly limited, and examples thereof include lithium ion batteries, lithium ion polymer batteries, lead storage batteries, nickel-hydrogen storage batteries, nickel-cadmium storage batteries, nickel-iron storage batteries, nickel-zinc storage batteries, silver oxide-zinc storage batteries, metal-air batteries, polyvalent cation batteries, condensers, and capacitors. Among them, a lithium ion battery is a suitable application. The heat absorber of this embodiment is also suitable for use in all-solid-state batteries as the secondary battery. The all-solid-state battery can also be ignited or damaged due to thermal runaway, and can expand and contract due to charging and discharging, just like the lithium ion battery, so that the effect of being equipped with the heat absorber of this embodiment can be achieved.
[0052] The secondary battery module capable of mounting the heat absorber of this embodiment is a secondary battery mounted on a moving object such as a vehicle or an aircraft (particularly a drone), and has a plurality of battery cells and a case for housing the plurality of battery cells. The battery cells (hereinafter also referred to as battery cells) constituting the secondary battery module can be battery cells in which a battery element including at least a positive electrode material layer, a negative electrode material layer, a separator, a positive electrode current collector, and a negative electrode current collector, etc., is enclosed within an exterior material, for example, a battery exterior film. A secondary battery module capable of mounting the heat absorber of this embodiment will be described below with reference to FIG. 1. FIG. 1 shows a cross-sectional view of a stacked battery 20 as an example of a secondary battery. The secondary battery capable of mounting the heat absorber of this embodiment is not limited to the flat stacked battery 20 as shown in FIG. 1. The secondary battery capable of mounting the heat absorber of this embodiment may be cylindrical, such as a wound secondary battery, or may be a cylindrical secondary battery deformed into a rectangular flat shape. In this embodiment, the stacked battery 20 has a structure in which a flattened, approximately rectangular battery element 10 in which a charge / discharge reaction substantially proceeds is sealed inside battery exterior materials 18a, b. The battery element 10 has a structure in which a positive electrode, an electrolyte layer (or separator) 14, and a negative electrode are stacked. The positive electrode has a structure in which a positive electrode material layer 11 containing a positive electrode active material is arranged on both sides of a positive electrode collector 12. The negative electrode has a structure in which a negative electrode material layer 16 containing a negative electrode active material is arranged on both sides of a negative electrode collector 17. One positive electrode material layer 11 and a negative electrode material layer 16 adjacent to the positive electrode material layer 11 are arranged to face each other via an electrolyte layer 14, and the positive electrode, the electrolyte layer 14, and the negative electrode are stacked in order. As a result, the adjacent positive electrode, the electrolyte layer 14, and the negative electrode form one single cell body. The stacked battery 20 shown in FIG. 1 has a structure in which a plurality of such single cell bodies are stacked and electrically connected in parallel. Also provided is an activated carbon layer 19 that adsorbs components derived from the positive electrode active material due to melting or sublimation of the positive electrode active material when the battery is exposed to high temperatures. 1, the positive electrode current collector 12 and the negative electrode current collector 17 are respectively attached with a positive electrode terminal 13 and a negative electrode terminal 15 for conducting the positive and negative electrodes, and are structured to be led out of the battery exterior materials 18a, b so as to be sandwiched between the ends of the battery exterior materials 18a, b. The positive electrode terminal 13 and the negative electrode terminal 15 can be attached to the positive electrode current collector 12 and the negative electrode current collector 17 of each electrode by welding or the like via a positive electrode lead and a negative electrode lead (not shown) as necessary. The battery exterior materials 18a and 18b are made of laminated films, and the sealant layers formed on the surfaces of the battery exterior materials 18a and 18b are usually heat-sealed to each other. Also, the battery exterior materials 18a and 18b have regions on their peripheries where the sealant layers are in close contact with each other by heat sealing.
[0053] Next, a secondary battery module equipped with the heat absorber of this embodiment will be described with reference to FIG. 2. FIG. 2 is a perspective view showing a schematic exploded state of the secondary battery module of FIG. 1. The battery element 10 shown in FIG. 2 has a configuration in which a positive electrode formed on a positive electrode current collector 12 (aluminum foil or the like) having a positive electrode terminal 13 and a negative electrode disposed on a negative electrode current collector 17 (metal foil or the like) having a negative electrode terminal 15 are stacked so as to face each other with a separator 14 containing an electrolyte interposed therebetween. Then, a plurality of battery elements 10 are stacked and sealed with battery exterior materials 18a, b (for example, aluminum laminate exterior body or the like). The heat absorber 1 of this embodiment is arranged so as to be in contact with the negative electrode current collector 17. The heat absorber 1 may be arranged so as to be in contact with not only the negative electrode current collector 17 but also the positive electrode current collector 12. Therefore, a secondary battery module having a heat absorber 1 mounted on a battery element 10 has one or more laminates in which a positive electrode formed on a positive electrode collector 12 (aluminum foil or the like) having a positive electrode terminal 13, a separator 14 containing an electrolyte, and a negative electrode arranged on a negative electrode collector 17 (metal foil or the like) having a negative electrode terminal 15 are sequentially laminated, and the one or more heat absorbers 1 can be arranged so as to abut against the positive electrode collector 12 and / or the negative electrode collector 17 but not against the separator 14. When a solid electrolyte or a gel electrolyte is used as the electrolyte, the electrolyte may be interposed between the electrodes instead of the separator 14. On the other hand, the hydrogel or aqueous solvent, which is the content of the heat absorber of this embodiment, does not come into direct contact with the battery element 10. Therefore, a suitable heat absorber for a secondary battery of this embodiment has a hydrogel and a bag filled with the hydrogel, but the content of the bag does not include the hydrogel or aqueous solvent so that the battery element 10 comes into direct contact with the hydrogel or aqueous solvent, and more preferably, the content of the bag of the heat absorber for a secondary battery does not include the battery element 10.
[0054] The secondary battery module of the present disclosure may have the heat absorber 1 of the present embodiment sandwiched between adjacent battery elements 10 (also referred to as battery cells) housed in a plurality of cases (not shown) or a plurality of battery exterior films 18a, b. The case may be made of, for example, aluminum, iron, or a metal material containing these, or a resin material such as polyphenylene sulfide, and being made of a resin material can contribute to reducing the weight of the secondary battery module. The heat absorber 1 can be sandwiched between the plurality of battery elements 10 by, for example, an adhesive, fusion (ultrasonic fusion, high-frequency fusion, heat fusion), pressure sensitive adhesive, or the like. With this configuration, the heat absorber 1 sandwiched between the battery elements 10 absorbs heat generated during charging of the secondary battery, thereby suppressing a sudden increase in temperature of the battery elements 10 and preventing deterioration, ignition, etc. of the battery elements 10. In addition, since the heat absorber 1 has a hydrogel that has absorbed an aqueous solvent as its content, when the heat absorber 1 is sandwiched between the battery elements 10, the heat insulating properties of the heat absorber 1 can suppress the temperature effect between the battery elements 10, and further, the cushioning properties of the swollen hydrogel act as a buffer for the volume change caused by the expansion of the battery elements 10, which is thought to facilitate mitigating the rise in internal pressure of the secondary battery module. EXAMPLES
[0055] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the examples given below.
[0056] (1) Evaluation method [Measurement of endothermic onset temperature, endothermic peak temperature and endothermic amount] For the hydrogel prepared in this example, the endothermic onset temperature and the endothermic peak temperature were measured as follows. Using a differential scanning calorimeter (DSC; DSC-7020 manufactured by Hitachi High-Tech Corporation), the temperature was raised from 20 ° C. to 350 ° C. at a rate of 1 ° C. / min under a nitrogen atmosphere, and the temperature at the intersection of a straight line extending the baseline on the low-temperature side of the DSC measurement curve to the high-temperature side and a tangent drawn at the point where the gradient of the curve on the low-temperature side of the endothermic peak associated with evaporation is maximum was taken as the endothermic onset temperature (° C.), and the point where the difference from the baseline of the DSC measurement curve is maximum was taken as the endothermic peak temperature (° C.). In addition, the integral value of the endothermic peak based on the baseline of the DSC measurement curve was divided by the mass of the endothermic agent used in the measurement to give the endothermic amount (J / g or mJ / mg).
[0057] [Evaluation of cushioning] Hydrogels were taken out from the heat absorbers (1) and (2) prepared in this example, and the cushioning properties were evaluated as follows. Specifically, the hydrogel was cut into a size of 10 cm length x 10 cm width x 1 cm height at room temperature (23°C), and placed in a tabletop precision universal testing machine (Shimadzu Corporation's "Autograph AGS-X") equipped with a 5 mm diameter indentation jig to carry out an indentation test. The indentation test was carried out by observing the return of the surface after 5 minutes of indentation at 1 MPa for 60 seconds and evaluating the results according to the following criteria. It returns to over 90% of its original height... Returns to 80% or more of the original height... Returns to 70% or more of the original height...△ It only returns to less than 70% of its original height... ×
[0058] [Flame retardancy evaluation] Each dispersion used in the examples was poured into a container with a thickness of 1 mm, and polymerization was carried out at 20° C. to obtain a sheet-like organic-inorganic composite hydrogel with a thickness of 1 mm. This sheet was cut into a size of 125 mm x 13 mm, and flame retardancy was evaluated by measuring the flame retardancy according to the 20 mm vertical flame test (IEC60695-11-10B, ASTM D38 01) of the UL94 flame test. Regarding flame retardancy, if it is V-1, there is no problem in practical use, and V-0 is preferable. Good condition: UL94 standard V-0 Passed: UL94 standard V-1 Failed: Less than UL94 standard V-1
[0059] [Evaluation of frost resistance] The heat endotherms (1) and (2) prepared in the examples are placed in a freezer at -20°C and left for 24 hours, after which the above-mentioned "Evaluation of cushioning properties" is carried out to evaluate the freeze resistance.
[0060] (2) Examples and Comparative Examples Example 1 In 100 parts by mass of pure water, 20 parts by mass of N,N-dimethylacrylamide (hereinafter abbreviated as "DMAA"), 4.8 parts by mass of water-swellable synthetic hectorite (manufactured by BYK Japan K.K., "Laponite RD"), 0.5 parts by mass of sodium peroxodisulfate (hereinafter abbreviated as "NPS"), and 0.8 parts by mass of N,N,N',N'-tetramethylethylenediamine (hereinafter abbreviated as "TEMED") were mixed and stirred to obtain a uniform dispersion (a-1) (see Table 1). Next, the dispersion liquid (a-1) was injected into a container made of an aluminum pouch (Mitsubishi Gas Chemical Company's "Gas Barrier Bag" 100 mm long x 300 mm wide x 0.094 mm thick, laminated with PET, aluminum foil and polyethylene) and the injection port was closed by heat sealing. The aluminum pouch was placed flat between gap materials 1 cm thick, a flat plate was placed on top of it and left at 20°C for 15 hours to produce a sheet-like heat absorber (1) 1 cm thick. Then, the obtained heat absorber (1) was evaluated according to the procedures described in the above [Evaluation of cushioning properties] and [Evaluation of flame retardancy]. The results are shown in Table 1. The swollen organic-inorganic composite hydrogel contained in the heat absorber (1) of Example 1 was taken out, and the endothermic peak temperature and endothermic amount were evaluated under the above-mentioned DSC measurement conditions. The DSC curve is shown in FIG.
[0061] Example 2 In 100 parts by mass of a mixed solution consisting of 80 parts by mass of pure water and 20 parts by mass of glycerin, 20 parts by mass of DMAA, 4.8 parts by mass of water-swellable synthetic hectorite (manufactured by BYK Japan, "Laponite RDS"), 0.5 parts by mass of NPS, and 0.8 parts by mass of TEMED were mixed and stirred to obtain a uniform dispersion (a-2). Then, a sheet-shaped heat absorber (2) was produced by the same method as in Example 1 above (see Table 1). Then, the obtained heat absorber (2) was evaluated according to the procedures described in the above [Evaluation of cushioning properties] and the above [Evaluation of flame retardancy]. The results are shown in Table 1. The swollen organic-inorganic composite hydrogel contained in the heat absorber (2) of Example 2 was taken out, and the endothermic peak temperature and endothermic amount were evaluated under the above-mentioned DSC measurement conditions. The DSC curve is shown in FIG.
[0062] [Table 1]
[0063] It was confirmed that the DSC measurement curves of the endotherms of Examples 1 and 2 descended from the start of the measurement. In addition, the endothermic onset temperatures of the endotherms of Examples 1 and 2 were determined from the DSC measurement curves according to the method for measuring the endothermic onset temperature described in the above section [Measurement of endothermic onset temperature, endothermic peak temperature, and endothermic amount]. As a result, the endothermic onset temperatures of the endotherms of Examples 1 and 2 were approximately 100°C for the endotherm (1) of Example 1, and approximately 125°C for the endotherm (2) of Example 2. Therefore, it was confirmed that the heat absorbers of Examples 1 and 2 have low endothermic onset temperatures and endothermic peak temperatures, and exhibit excellent endothermic amounts, cushioning properties, and flame retardancy. In addition, when the heat absorbers (1) and (2) of Examples 1 and 2 were placed in a freezer at -20°C and left for 24 hours, and then removed from the refrigerator to evaluate the cushioning properties, the heat absorber (1) of Example 1 had a reduced cushioning property, but the heat absorber (2) of Example 2 maintained its cushioning property, and therefore the heat absorber (2) of Example 2 had excellent freeze resistance. In this embodiment, if there is no bag containing the hydrogel or aqueous solvent, the contents, that is, the hydrogel or aqueous solvent, will dissipate, and therefore sufficient heat absorption effect, flame retardancy, and cushioning properties cannot be obtained when the temperature of the battery rises or as time passes. However, the heat absorber of this embodiment prevents the hydrogel from dissipating because the filled contents remain inside the bag, and sufficient heat absorption effect, flame retardancy, and cushioning properties can be obtained when the temperature of the battery rises or as time passes.
[0064] [Explanation of symbols] 1. Laminate 10 Battery elements 11 Cathode material layer 12 Positive electrode current collector 13 Positive terminal 14 Electrolyte layer (or separator) 15 Negative terminal 16 Negative electrode material layer 17 Negative electrode current collector 18a,b Battery exterior material 19 Activated carbon layer 20 Stacked battery
Claims
1. The device has a bag that can be filled with a content, and a hydrogel that is filled in the bag as the content, The water vapor permeability ([g / (m 2 ·24 h)]) of the sheet constituting the bag body is greater than 0 g / (m 2 ·24 h) and not greater than 50 g / (m 2 ·24 h); The hydrogel is an organic-inorganic composite hydrogel made from at least a water-soluble organic monomer and a water-swellable clay mineral as reaction raw materials, and the content of the hydrogel is in the range of 20% by mass to 100% by mass with respect to the total amount of the contents of the bag, and the heat absorption onset temperature is 160°C or lower.
2. The heat sink according to claim 1 , wherein the hydrogel has a cushioning property of 90% or more as determined by the following evaluation method. Evaluation method: At room temperature (23°C), the hydrogel was cut into a size of 10 cm length x 10 cm width x 1 cm height, and placed in a tabletop precision universal tester equipped with a 5 mm diameter pressing tool. The hydrogel was pressed at 1 MPa for 60 seconds, and then the degree to which the hydrogel surface returned to its original height after 5 minutes had elapsed was evaluated.
3. The heat absorber described in claim 1, wherein the content of the water-swellable clay mineral contained in the dispersion liquid (a) containing the reaction raw materials, i.e., the water-soluble organic monomer and the water-swellable clay mineral, a polymerization initiator, and an aqueous solvent, is in the range of 0.1 mass % to 50 mass % relative to the total amount (mass) of the water-soluble organic monomer, the water-swellable clay mineral, and the aqueous solvent.
4. The heat absorber described in claim 1, wherein the amount of heat absorbed at the endothermic peak temperature (in the range of 80°C to 160°C) is in the range of 100 J / g or more and 3000 J / g or less.
5. The heat absorber according to any one of claims 1 to 4, further comprising a low-volatility solvent as the content.
6. The heat absorber according to any one of claims 1 to 4, which is used in a secondary battery.
7. A secondary battery module comprising the heat absorber according to any one of claims 1 to 4.
8. The secondary battery module according to claim 7 , wherein the heat sink is sandwiched between battery cells.
9. 8. The secondary battery module according to claim 7, wherein the heat sink has a total thickness in the range of 100 to 50,000 μm.
Citation Information
Patent Citations
Organoinorganic composite polymer gel and preparation process of the same
JP2006028446A
Battery including coolant, and battery pack including coolant
JP2012048905A
Transport container with flame retardant layer and heat blocking layer
JP2017534531A
Biomedical energization elements with polymer electrolytes
JP2018067546A
Fire-resistant resin composition, fireproof sheet, and battery
JP2020132843A